Transformasi Permainan Tradisional Menjadi Bahan Ajar yang Relevan pada Jenjang Pendidikan Dasar - Muhammad Syahru Romadhon (UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to investigate the potential of traditional games as effective pedagogical tools for primary school students. Employing a qualitative literature review methodology, this article compiles and analyzes various scholarly sources concerning the advantages, challenges, and strategies for converting traditional games into educational materials. The findings indicate that traditional games possess significant educational value across cognitive, motor, social, and character development domains for children. Nonetheless, their implementation in educational settings remains limited, primarily due to the insufficient guidance and training available for educators. The adaptation of traditional games into teaching materials can be achieved through their integration into learning modules, digital educational resources, or interactive classroom activities. This study advocates for the systematic and replicable development of teaching materials rooted in local culture, alongside ongoing professional development for educators. With appropriate transformation, traditional games can not only enhance pedagogical methods but also reinforce cultural identity and instill noble values in students from an early age.